2016
DOI: 10.1038/onc.2016.75
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB-HOTAIR axis links DNA damage response, chemoresistance and cellular senescence in ovarian cancer

Abstract: The transcription factor nuclear factor kappa B (NF-κB) and the long non-coding RNA (lncRNA) HOTAIR (HOX transcript antisense RNA) play diverse functional roles in cancer. In this study, we show that upregulation of HOTAIR induced platinum resistance in ovarian cancer, and increased HOTAIR levels were observed in recurrent platinum-resistant ovarian tumors vs. primary ovarian tumors. To investigate the role of HOTAIR during DNA damage induced by platinum, we monitored double-strand breaks and show that HOTAIR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
147
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(153 citation statements)
references
References 57 publications
6
147
0
Order By: Relevance
“…For instance, DNA is the key target of traditional chemotherapy drugs such as platinum, and cancer cells tend to be more resistant to platinum as a result of abnormal DNA damage repair activation [28, 29]. A latest study has observed that NF-κB/HOTAIR have interaction in DNA damage response in development of chemoresistance [30]. Accordingly, specific inhibition of DNA repair is believed to improve the efficacy of chemotherapeutics.…”
Section: Mechanisms Of Cancer Cell Drug Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, DNA is the key target of traditional chemotherapy drugs such as platinum, and cancer cells tend to be more resistant to platinum as a result of abnormal DNA damage repair activation [28, 29]. A latest study has observed that NF-κB/HOTAIR have interaction in DNA damage response in development of chemoresistance [30]. Accordingly, specific inhibition of DNA repair is believed to improve the efficacy of chemotherapeutics.…”
Section: Mechanisms Of Cancer Cell Drug Resistancementioning
confidence: 99%
“…The ectopic expression of HOTAIR could persistently repair DNA damage attributed by platinum, and it activated NF-κB signaling. It is suggested that NF-κB/HOTAIR crosslinking contributed to chemoresistance in ovarian cancers [30]. …”
Section: Long Non-coding Rna In Cancer Cell Drug Resistancementioning
confidence: 99%
“…Furthermore, they demonstrated the presence of a positive-feedback loop that induces HOTAIR. This activates DDR and sustains NF-κB expression (115). Recently, Yoon et al reported a function of lncRNA HOTAIR as a scaffold for ubiquitin-mediated proteolysis in posttranslational control (116).…”
Section: Maintenance Of Senescencementioning
confidence: 99%
“…STAT3 promotes the transcription of lin-28, a post-transcriptional inhibitor of Let-7 miRNA biogenesis, while NF-κB was recently shown to activate the transcription of DICER. 87,101 However, it is still unclear whether STAT3/NF-κB physically interacts with the players of the miRNA biogenesis pathway. The second key question is what are the long non-coding RNAs that are transcriptionally controlled by NF-κB/STAT3?…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Given the recent study demonstrating the activation of the NF-κB pathway by HOTAIR in ovarian cancer chemo resistance, it is tempting to speculate a similar mechanistic link between NF-κB and HOTAIR in ESCC. 87 In addition to the upstream regulation of NF-κB by lncRNAs, the study by Liu et al 88 profiled the non-coding interacting partners of this complex in cancer. This led to the identification of NF-κB interacting lncRNA (NKILA) which is upregulated by NF-κB, binds to NF-κB/IκB complex directly inhibiting IKK induced phosphorylation and activation of NF-κB pathway.…”
Section: Non-coding Rnas Regulating/ Regulated By Nf-κb Pathway In Esccmentioning
confidence: 99%